2014
DOI: 10.1016/j.aju.2014.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the amount of residual urine in men with bladder outlet obstruction: Could it be a predictor for bladder contractility?

Abstract: ObjectiveTo determine from urodynamic data what causes an increased postvoid residual urine volume (PVR) in men with bladder outlet obstruction (BOO), urethral resistance or bladder failure, and to determine how to predict bladder contractility from the PVR.Patients and methodsWe analysed retrospectively the pressure-flow studies (PFS) of 90 men with BOO. Nine patients could not void and the remaining 81 were divided into three groups, i.e. A (30 men, PVR < 100 mL), B (30 men, PVR 100–450 mL) and C (21 men, PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
9
0
6
Order By: Relevance
“…As one of the progressive manifestations and the most serious complications of BPH, AUR implies that the bladder function has been decompensated (Elmissiry et al, 2019), which occurs because of the bladder outlet obstruction. At this stage, even if surgical treatment can relieve the obstruction to a certain extent, the patient's bladder function will still be severely impaired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the progressive manifestations and the most serious complications of BPH, AUR implies that the bladder function has been decompensated (Elmissiry et al, 2019), which occurs because of the bladder outlet obstruction. At this stage, even if surgical treatment can relieve the obstruction to a certain extent, the patient's bladder function will still be severely impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Once it occurs, AUR will seriously affect the quality of life and becomes the primary reason for surgical operation. The occurrence of AUR predicts the decompensation of bladder function, which is closely related to the patient's prognosis (Elmissiry, Ali, Abulfotooh, Moussa, & Ali, 2019; Tubaro et al., 2003). Prior reported studies have shown that patients with a history of AUR have a worse curative effect of transurethral resection of the prostate than patients without a history of AUR (Chen et al., 2012; Wagenlehner et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A three‐stage model can be hypothesized to characterize BOO‐induced bladder remodeling in humans: hypertrophy, compensation (increased detrusor contractility during the voiding phase, often in combination with filling phase detrusor overactivity) followed by the phase of decompensation (detrusor underactivity) . Decompensation and progression to BD correlate with severity and duration of BOO …”
Section: How Do Histological and Biochemical Changes In The Bladder Cmentioning
confidence: 99%
“…Moreover, AUR has been one of the most common reasons for surgical treatment. AUR suggests the presence of a decompensation of bladder function, and bladder dysfunction directly affects patients' prognosis (5,6). An increasing number of studies have shown that, compared with patients without a history of AUR, the efficacy of surgery for BPH patients with a history of AUR is significantly worse (7).…”
Section: Introductionmentioning
confidence: 99%